Identification of the Crucial Gene in Overflow Arteriovenous Fistula by Bioinformatics Analysis - Zhao, Zhengde; Fu, Qining; Hu, Liangzhu; Liu, Yangdong (Frontiers in Physiology, 2021)
Objective: Preliminary screen the crucial genes in venous segment intimal hyperplasia of AV fistula and underlying potential molecular mechanisms of intimal hyperplasia with bioinformatics analysis Methods: The gene expression profile data (GSE39488) was analyzed to identify differentially expressed genes (DEGs). We performed Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis of DEGs. Gene Set Enrichment Analysis (GSEA) was used to understand the potential activated signaling pathway. The protein-protein interaction (PPI) network was constructed with the STRING database and Cytoscape software. The Venn diagram between ten hub genes and gene sets of four crucial signaling pathways were used to obtain core genes and relevant potential pathway. Further GSEA analyses were performed to understand their biological function. Results: A total of 185 DEGs were screened in this study. The main biological function of the 111 up-regulated genes in AV fistula primarily concentrated on cell proliferation and vascular remodeling; the 74 down-regulated genes in AV fistula were enriched in the biological function mainly relevant with inflammation. GSEA analysis found four signaling pathways crucial for intimal hyperplasia, including MAPK, NOD-like, Cell Cycle, and TGF-beta signaling pathway. Ten hub genes were identified, including EGR1, EGR2, EGR3, NR4A1, NR4A2, DUSP1, CXCR4, ATF3, CCL4, CYR61. Particularly, DUSP1 and NR4A1 were identified as core genes that potentially participate in the MAPK signaling pathway. In AV fistula, the biological process and pathways were primarily involved with MAPK signaling pathway and MAPK mediated pathway with high-expression of DUSP1; and were majorly relevant with cell proliferation and inflammation with low-expression of DUSP1. Besides, the biological process and pathways in AV fistula with high-expression of NR4A1 similarly included MAPK signaling pathway and the pathway mediated by MAPK signaling, and it was mainly involved with inflammation in AV fistula with low-expression of NR4A1. Conclusion: We screened four potential signaling pathways relevant to intimal hyperplasia and identified ten hub genes, including two core genes (DUSP1 and NR4A1). Two core genes potentially participate in the MAPK signaling pathway and might serve as the therapeutic targets of intimal hyperplasia to prevent stenosis after fistula creation.